SEBARAN WAKTU REALISASI ANGGARAN BELANJA MODAL: STUDI FENOMENOLOGI PADA SEKRETARIAT DAERAH KABUPATEN GIANYAR - Krisnawati, A.A Ari; Sudana, I Putu; Wirama, Dewa Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.08.TAHUN 2017DO - 10.24843/EEB.2017.v06.i08.p03, 2017)
The phenomenon underliying of the research is realization of capital expenditure at the Regional Secretary of Gianyar Regency is disproportionately distributed due to the tendency of the realization that significantly increases toward the end of fiscal year. Using the method of transcendental phenomenology of Husserl, the researcher explores the meaning and essence that become the cause of the phenomenon. This approach states that the phenomenon can only be observed by those who experienced the phenomenon. In order to determine the cause of the phenomenon originally, the researcher seek information from numbers of informants who are directly related to the phenomenon. The information obtained is then elaborated through epoche proces, until it reaches the core of the phenomenon. The result of epoche process is that budget planning is the main factor causing the temporal distribution at capital expenditure becomes disproportionate and tend to be concentrated at the end of fiscal year.
Keywords: Capital expenditure budgetes realization, phenomenon, Budget Planning